Peran Penting Keluarga Dalam Masa Perkembangan Anak – Anak - Ramadhani, Latifa Nur; Wardani, Rofico Eka; Choiruroziqin, Bayu (Jurnal Ilmiah Wahana Pendidikan, 2024)
Educators in the review of professionalism is a major factor in improving the quality of education to shape the intellectual and personal development of learners, thus creating a good and bad personal normative learners. Education in the child acquired not only in school, but all of the factors may be used as a source of education, especially in the family environment can be a major factor to the development of children. The family environment plays an important role and influence on the success of student achievement.